TOWARDS DOING PRACTICAL INTEGRAL MISSION: - V Magezi; C Mutowa (Acta Theologica)
The concept “integral mission” denotes the contribution of churches in helping people and communities with material resources. It remains unclear as to how this widely held theological concept is done practically. At a theological level, there has been a general silence on reflection regarding how organisations can practically do integral mission. Using an institutional theological understanding of compassionate ministry within the church of the Nazarene Compassionate Ministries (NCM), this article demonstrates the convergences and divergences that may arise in an organisation as it attempts to implement integral mission interventions. It is also an empirical case study of leadership and grassroots (implementation) level staff to show the differences that may exist and weaken integral mission efforts. At a theory formation level, the article contributes to understanding the dynamics of implementing integral mission.